Effects of ejector geometries on performance of ejector-expansion R410A air conditioner considering cooling seasonal performance factor. (1st November 2017) - Jeon, Yongseok; Jung, Jongho; Kim, Dongwoo; Kim, Sunjae; Kim, Yongchan
Highlights: The performance of an ejector-expansion R410A air conditioner is measured. The effect of ejector geometries on the COP and CSPF is analyzed. The mixing-section diameter of the ejector is optimized based on the CSPF. The mixing-section diameter is optimized based on the climatic conditions. Abstract: The objective of this study was to investigate the effects of ejector geometries on the performance of an ejector-expansion air conditioner (EEAC) considering the cooling seasonal performance factor (CSPF). The performance of the EEAC using R410A was measured and analyzed by varying the compressor speed, outdoor-bin temperature, operating pressures, nozzle-throat diameter, and mixing-section diameter. The EEAC in the medium-capacity mode exhibited maximum coefficient of performance (COP) improvement, i.e., 7.5%, over the baseline (conventional) cycle. The optimum mixing-section diameter was determined to be 9 mm based on the CSPF. In addition, the optimum mixing-section diameter increased with an increase in the annual average outdoor temperature. The CSPF of the EEAC with the optimized mixing-section diameter improved in the range of 16.0–20.3% over the baseline cycle depending on the climatic conditions.